The effect of uniaxial compressive and tensile strains on the structural, dynamical, electronic, and optical properties of ZrCl2 monolayer: Ab-initio calculations - Hind Alqurashi; Bothina Hamad; M.O. Manasreh (Chemical Physics Impact)
Recently, the two-dimensional material zirconium dihalide (ZrCl2) has received a significant attention for prospective device applications due to its unique electronic, mechanical, magnetic, and topological properties. This work reports theoretical predictions for the structural, dynamical, electronic, and optical properties of ZrCl2 under uniaxial compressive and tensile strains using density functional theory (DFT). The band gap structures were found to be highly sensitive to the uniaxial compressive and tensile strains of ZrCl2 monolayer (ML). The unstrained ZrCl2 ML has a semiconducting behavior with an indirect band gap of 1.19 eV. Under the uniaxial compressive tensile stress (εx) of −6%, −4%, −2%, the ZrCl2 ML retains the semiconducting behavior with indirect band gaps of 0.00, 0.30, 0.73, respectively. However, the ZrCl2 ML has a semiconductor behavior with direct band gaps of 0.91, 0.56, and 0.41 eV for applied tensile strains of 2%, 4%, and 6%, respectively. In addition, the optical properties of ZrCl2 ML are calculated, and the optical absorption is found to exhibit a significant anisotropy in the photon energy range of 0 - 13 eV. Based on the result of the optical properties, a ZrCl2 ML is expected to potentially be a candidate for optoelectronic applications, such as an infrared photodetector.